Hearing Loss in Cryptococcal Meningitis Survivors. (4th October 2017) - Lofgren, Sarah; Montgomery, Martha; Yueh, Nathan; Namudde, Alice; Rhein, Joshua; Abassi, Mahsa; Musubire, Abdu; Meya, David; Boulware, David; ,
Abstract: Background: Hearing loss is a known complication cryptococcal meningitis (CM); however, there is a paucity of data. We aimed to describe hearing loss in CM survivors. Methods: We assessed hearing via audiometry 8 and 18 weeks after diagnosis of CM in Kampala, Uganda from 2015-2016. We measured at 0.5, 1, 2, 4 Hz. Normal hearing was defined as minimum hearing level at <25 decibels (dB), mild at 25-39, moderate hearing at 40–69, severe at 70–89, and profound hearing loss at 90+ dB. We compared clinical factors, fungal burden, and CSF parameters to evaluate for factors associated with improvement (change in hearing loss category). Results: We evaluated hearing symptoms via audiogram at week 8 ( n = 117) and week 18 ( n = 98). At 8-weeks, 6 (5%) participants had normal hearing, 36 (31%) had mild hearing loss, 72 (62%) had moderate hearing loss, 3 (3%) had severe hearing loss and none had profound hearing loss. Of those with moderate/severe/profound loss at week 8, 63 (54%) had mixed conductive + sensorineural hearing loss, 15 (13%) had sensorineural hearing loss, and 14 (12%) had conductive hearing loss. An additional 19 (16%) had sensorineural loss but unknown air conduction, and 3 (3%) did not have sensorineural loss but unknown air conduction. We compared risk factors for hearing loss summarized in Table 1. We assessed 66 participants who had repeated audiograms at week 8 and week 18. Of those 31 (47%) had no change, 30 (45%) had improvement and 5 (8%) had worsening. Conclusion: Moderate/severe hearing loss was common 8 weeks after diagnosis of CM. More than half had mixed hearing loss and 20% had conductive hearing loss which represents a higher incidence than noted in other types of meningitis. The data is complicated by advanced HIV. Further research is needed evaluating immunologic factors causes hearing impairment in those who survived CM. Disclosures: All authors: No reported disclosures.